2017
DOI: 10.1155/2017/6418048
|View full text |Cite
|
Sign up to set email alerts
|

Yacon (Smallanthus sonchifolius) Leaf Extract Attenuates Hyperglycemia and Skeletal Muscle Oxidative Stress and Inflammation in Diabetic Rats

Abstract: The effects of hydroethanolic extract of Yacon leaves (HEYL) on antioxidant, glycemic, and inflammatory biomarkers were tested in diabetic rats. Outcome parameters included glucose, insulin, interleukin-6 (IL-6), and hydrophilic antioxidant capacity (HAC) in serum and IL-6, HAC, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in soleus. The rats (10/group) were divided as follows: C, controls; C + Y, HEYL treated; DM, diabetic controls; and DM + Y, diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 47 publications
1
26
0
26
Order By: Relevance
“…Yacon leaves extract attenuates hyperglycemia, oxidative stress and inflammation in diabetic rats [5]. A decoction of yacon leaves reduced blood glucose level in streptozotocin induced diabetic rats and increased the insulin concentration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yacon leaves extract attenuates hyperglycemia, oxidative stress and inflammation in diabetic rats [5]. A decoction of yacon leaves reduced blood glucose level in streptozotocin induced diabetic rats and increased the insulin concentration [6].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, there is extensive evidence that the hyperglycemia established in the diabetic condition is associated with the generation of reactive oxygen species (ROS) and a weakening of the antioxidant defense, resulting in enhanced oxidative stress [ 13 , 34 ]. Indeed, the activity of several antioxidant enzymes is decreased in the diabetic heart in both rats and humans [ 13 , 35 , 36 ]. Here, we have demonstrated that the activity of the antioxidant enzymes catalase, superoxide dismutase, and glutathione peroxidase is decreased in the diabetic group and MDA concentration is elevated in cardiac tissue (Figures 2(a) – 2(d) ), indicating an oxidative stress process.…”
Section: Discussionmentioning
confidence: 99%
“…The solvents were evaporated to dryness under low pressure (45°C) using a rotary evaporator in a vacuum system to afford the crude Yacon leaf extract (YLE). More information about the plant material, production of leaf extract, and phytochemical characterization can be found in a previous study of our group [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations